Konsep Kejujuran dan Keadilan dalam Al-Qur’an (Studi Tafsir Tematik) - Ilma Aurelly; Nur Kholillah; Ana Rahmawati (ejournal.nurulqadim.ac.id, 2024)
This study focuses on the interpretation of the concepts of honesty and justice in the Qur'an which is a key element in islamic interpretation. In the verse of the Qur'an, it highlights the importance of honesty and justice as the foundation in human relations and relationships with Allah SWT. This study aims to deepen our knowledge about the interpretation of verses of the Qur'an related to the theme of